Crizotinib and ceritinib trigger immunogenic cell death via on-target effects - Adriana Petrazzuolo (Taylor & Francis Group, 2021)
Immunogenic cell death (ICD) has initially been discovered in the context of chemotherapy. High-dose crizotinib also stimulates ICD, as we described for non-small cell lung cancer lacking activating chromosomal aberrations of ALK or ROS1, the usual targets of crizotinib, indicating that crizotinib may act through off-target effects. However, we found that low-dose of ALK inhibitors, crizotinib and ceritinib, may stimulate ICD in anaplastic large cell lymphoma, in which ALK is activated due to a chromosomal translocation, suggesting on target ICD-promoting effects.